Urban environmental crisis management - Song, Yajie; Zheng, Youfei; Li, Jian (Science Press Alpha Science International, 2012)
The Urban Environmental Crisis Management (UECM) research initiated by Yale University and its partners from the Chinese Academy of Sciences, Peking, Tianjin (TUT), Nanjing (NUIST), Liaoning University and others in China has global significance and is in urgent demand. This book systematically surveys, analyzes, and explores better ways to enhance urban environmental crisis management. The UECM research combines with the studies on regional ecosystem stability and symbiosis (RESS) for urban regional harmony and sustainability, providing an important tool and reference for urban ecosystem management research and advancement, including theories, practices, policies, mentors, cases and comparative studies along with the UECM research progress in China and at Yale.